Efektivitas Metil Eugenol Terhadap Penangkapan Lalat Buah (Bactrocera dorsalis) Pada Pertanaman Cabai - John A Patty (Faculty of Agriculture, Pattimura University, 2012)
One of the major constraints in chili production system in Indonesia is the fruit fly attack on chili fruits. These pests often lead to crop failure if not treated seriously. One way used to suppress the pest population is the use of Methyl Eugenol attractant compound (Petrogenol 800 L). The study was conducted to determine the effect of methyl eugenol dose and catching time difference on fruit flies that were caught. The study took place in Waimital Village, Kairatu Subdistrict, West Seram District. The research was conducted in an experiment using a Randomized Block Design (RAB) with 5 treatments, namely: (A) 0.5 ml of methyl eugenol, (B) 1 ml of methyl eugenol, (C) 1.5 ml of methyl eugenol, (D) 2 ml methyl eugenol, (E) 2.5 ml of methyl eugenol, placed in a each trap. Observations were conducted when the insects were active at 10.00 (06.00-10,00 period) and when the insects were inactive at 18:00 hours (11:00 to 18:00 period) on the number of fruit fly imagoes that were captured. The results showed that the effective methyl eugenol dose to catch Bactrocera dorsalis was in treatment C (1.5 ml, with 32.53 fruit flies caught per day or 97.67 fruit flies catches during three days of observation. The highest number of catch for 3 days was at 2,5 ml, with 118.60 fruit flies caught.